2007
DOI: 10.1007/s10722-007-9244-3
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide genotyping of castor bean germplasm (Ricinus communis L.) using AFLPs and SSRs

Abstract: Worldwide genetic diversity in 200 individuals comprising 41 castor bean accessions was assessed using amplified fragment polymorphisms (AFLPs) and simple sequence repeats (SSRs). We found that, despite surveying five continents and 35 countries, genetic diversity in castor bean germplasm is relatively low (overall H e = 0.126 for AFLPs and 0.188 for SSRs) compared to estimates of genetic diversity in other plant species. Our data also show no geographic structuring of genotypes across continents or countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
92
4
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 45 publications
12
92
4
3
Order By: Relevance
“…Studies also confirm that Ricinus species does not have a specific genetic pattern or markers that do not allow differentiation based on geographical origin and DNA fragments do not appear to be associated with differentiation of population (Pecina-Quintero et al 2013). The first report which came out with low polymorphism indicated the narrow genetic base (Allan et al 2008). Milani et al (2009) studied diversity structure based on phenotypic traits and RAPD markers.…”
Section: Polymorphism Of Est-ssrsmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies also confirm that Ricinus species does not have a specific genetic pattern or markers that do not allow differentiation based on geographical origin and DNA fragments do not appear to be associated with differentiation of population (Pecina-Quintero et al 2013). The first report which came out with low polymorphism indicated the narrow genetic base (Allan et al 2008). Milani et al (2009) studied diversity structure based on phenotypic traits and RAPD markers.…”
Section: Polymorphism Of Est-ssrsmentioning
confidence: 96%
“…PIC values for the tested primers varied from a low of 0.27 (Rc DES 596) to a high of 0.49 (Rc DES 592) with an average value of 0.332. Allan et al (2008) reported 9 genomic SSR markers, 0.403 gene diversity (PIC) with an average of 3.01 alleles per locus. Bajay et al (2009) developed 12 genomic SSR markers with an average of 0.416 gene diversity (He) and 3.3 alleles per locus.…”
Section: Polymorphism Of Est-ssrsmentioning
confidence: 99%
“…The lack of adequate genetic variation has limited jatropha improvement (Allan et al 2008, Sun et al 2008, Trebbi et al 2015.One effective way to create genetic variability and incorporate desirable traits is by wide hybridization.The study addressed a combination of desirable traits of the two genera related to seed yield, oil content and quality, and to synchronous maturity. Their segregating progenies, if available, are expected to be an excellent germplasm source for genetic improvement of both crops in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have been carried out on the genetic diversity and phylogenetics of castor using molecular markers. Recently, studies have been initiated on assessment of genetic variation in castor germplasm using AFLP and SSR markers (Allan et al, 2008). The aim of this study was to detect genetic variability among the set of 30 castor genotypes using 6 RAPD markers.…”
Section: Introductionmentioning
confidence: 99%